2006
DOI: 10.1038/sj.tpj.6500366
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate stimulates glucose transport through AMP-activated protein kinase-mediated pathway in L6 skeletal muscle cells

Abstract: The use of topiramate (TPM) in the treatment of binge-eating disorder, bulimia nervosa, and antipsychotic-induced weight gain has recently increased, however, the exact molecular basis for its effects on body weight reduction and improved glucose homeostasis, is yet to be elucidated. Here we investigated the effect and signaling pathway of TPM on glucose uptake in L6 rat skeletal muscle cells, which account for 470% of glucose disposal in the body. Intriguingly, we found that TPM (10 mM) stimulated the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…3A). Ha et al (2006) reported that topiramate stimulated the rate of glucose transport in L6 skeletal muscle cells. From these results, we suggest that G. lucidum extract also increases glucose uptake by stimulating AMPK activity in skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…3A). Ha et al (2006) reported that topiramate stimulated the rate of glucose transport in L6 skeletal muscle cells. From these results, we suggest that G. lucidum extract also increases glucose uptake by stimulating AMPK activity in skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both basal or insulin‐stimulated glucose uptake and insulin signalling in insulin‐sensitive or insulin‐resistant cultured muscle cells (differentiated C2C12 myotubes) were not affected by topiramate. Our data are in contrast to a previous study that reported that topiramate increases glucose uptake in cultured insulin‐sensitive L6 cells, a rat skeletal muscle cell line, via an AMPK‐mediated pathway (Ha et al ., ). The phosphorylation level of AMPK (Thr172) was not increased when we treated C2C12 myotubes with topiramate (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…The weight‐lowering mechanism of topiramate remains uncertain, but seems to involve both central and peripheral targets. Topiramate acts peripherally by enhancing insulin sensitivity and activating AMP‐kinase (AMPK) and acetyl‐CoA carboxylase in skeletal muscles, whereas its central effect is mainly exerted in the hypothalamus where it potentiates both leptin‐induced Jak‐Stat and MAPK/ERK and insulin‐induced insulin receptor substrate/Akt/forkhead box O1 pathway activation . These effects on leptin and insulin signalling ultimately lead to an increase in the transcription of genes encoding for anorectic peptides including POMC, thyrotropin‐releasing hormone (TRH), and corticotropin‐releasing hormone (CRH) .…”
Section: Phentermine/topiramate Combinationmentioning
confidence: 99%